1995
DOI: 10.1007/bf00010282
|View full text |Cite
|
Sign up to set email alerts
|

Initial responses of maize and beans to decreased concentrations of monomeric inorganic aluminium with application of manure or tree prunings to an Oxisol in Burundi

Abstract: Prunings of Calliandra calothyrsus, Grevillea robusta, Leucaena diversifolia and farm yard manure were applied each cropping season at 3 and 6 t dry matter ha-1 to an Oxisol in Burundi. The field plots also received basal applications of nitrogen (N), phosphorus (P) and potassium (K). Application of the tree prunings or farm yard manure decreased the concentration of monomeric inorganic aluminium (A1) in soil solution from 2.92 mg A1 din-3 in the control plots to 0.75 mg A1 dm-3 in the plots receiving 6 t ha-l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
5

Year Published

1995
1995
2014
2014

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(15 citation statements)
references
References 20 publications
(27 reference statements)
1
9
0
5
Order By: Relevance
“…Given that 63% of pasture, 87% of wheat, 89% of dairy soil samples appear to contain Colwell P concentrations above the CV for 90-95% of maximum production, yields are more likely to be constrained by other factors such as lack of water, soil acidity, and other nutrient deficiencies (Table 3). Practices to ameliorate many of these other constraints already exist, including (i) the application of liming materials to manage soil acidity (Snars et al 2004;Wong et al 1998;Wong et al 1995), (ii) improving water holding and P retention, and reducing Colwell P/PBI of sandy soils (Wong and Asseng 2006;Vlahos et al 1989;Summers et al 1993), (iii) relieving subsoil constraints to root growth to capture some leached P (Wong and Asseng 2007), and (iv) using techniques to identify site specific nutrient needs (Wong et al 2001(Wong et al , 2008(Wong et al , 2010.…”
Section: Discussionmentioning
confidence: 99%
“…Given that 63% of pasture, 87% of wheat, 89% of dairy soil samples appear to contain Colwell P concentrations above the CV for 90-95% of maximum production, yields are more likely to be constrained by other factors such as lack of water, soil acidity, and other nutrient deficiencies (Table 3). Practices to ameliorate many of these other constraints already exist, including (i) the application of liming materials to manage soil acidity (Snars et al 2004;Wong et al 1998;Wong et al 1995), (ii) improving water holding and P retention, and reducing Colwell P/PBI of sandy soils (Wong and Asseng 2006;Vlahos et al 1989;Summers et al 1993), (iii) relieving subsoil constraints to root growth to capture some leached P (Wong and Asseng 2007), and (iv) using techniques to identify site specific nutrient needs (Wong et al 2001(Wong et al , 2008(Wong et al , 2010.…”
Section: Discussionmentioning
confidence: 99%
“…Extractable Al levels were reduced to well below the toxic level for rice (Willett and Intrawech, 1988). The decreased levels of exchangeable Al might be associated with the formation of non-toxic organic-Al complexes when straw was added (Bessho and Bell, 1992;Wong et al, 1995) in addition to the higher soil pH maintained with straw addition.…”
Section: Intermittently Flooded Conditionsmentioning
confidence: 93%
“…Reduced Al toxicity to maize, in addition to increased supply of nitrogen, could be responsible for the favorable response of HI in these situations. Many studies have indicated the reduction of Al toxicity with the addition of such a large amount of organic residues because their decomposition products would bind Al and reduce Al saturation (Wong et al, 1995).…”
Section: Effect On Crop Yieldsmentioning
confidence: 99%